Individualno izdelano fleksibilno ležišče iz silikona za transfemoralno protezo - Angeloska Petrušić, Lea (Rehabilitacija (Ljubljana), 2016)
Background: Socket is the most important part of the prosthesis. To provide the correct transmission of the forces it must be manufactured appropriately and must be comfortable for the patient. There are many types of sockets and they can be made from different materials. We created a flexible socket out of silicone, and compared that process with the manufacturing process of thermoplastic socket. We also evaluated patient satisfaction with both sockets. Methods: We compared the manufacturing process for both sockets. To assess satisfaction with the prosthesis, we used the Quebec User Evaluation of Satisfaction with Assistive Technology questionnaire. For assessment of satisfaction, we used the Prosthetic Socket Fit Comfort Score scale. We also measured the flexibility of the hip joint with two sockets. Results: Both sockets were manufactured in a similar procedure, the difference is in the time of manufacturing. The patient saw the biggest difference in the comfort of the socket made of silicon. The patient also made the largest flexion movement with the flexible silicon socket. Conclusion: Custom-made silicone socket is more comfortable than the standard prosthetic sockets. It allows more movement and exerts less pressure in groin while sBackground: Socket is the most important part of the prosthesis. To provide the correct transmission of the forces it must be manufactured appropriately and must be comfortable for the patient. There are many types of sockets and they can be made from different materials. We created a flexible socket out of silicone, and compared that process with the manufacturing process of thermoplastic socket. We also evaluated patient satisfaction with both sockets. Methods: We compared the manufacturing process for both sockets. To assess satisfaction with the prosthesis, we used the Quebec User Evaluation of Satisfaction with Assistive Technology questionnaire. For assessment of satisfaction, we used the Prosthetic Socket Fit Comfort Score scale. We also measured the flexibility of the hip joint with two sockets. Results: Both sockets were manufactured in a similar procedure, the difference is in the time of manufacturing. The patient saw the biggest difference in the comfort of the socket made of silicon. The patient also made the largest flexion movement with the flexible silicon socket. Conclusion: Custom-made silicone socket is more comfortable than the standard prosthetic sockets. It allows more movement and exerts less pressure in groin while sitting and bending over.
Keywords: Amputation; flexible prosthetic socket; nadkolenska amputacija; Prostheses and Implants; proteze; silikon; trans-femoral amputation; transfemoralna proteza